Integrating Sri Aurobindo's Educational Philosophy Into Research Practices: A Transformative Approach For Researchers (International Journal of Food and Nutritional Sciences, 2022)
Today in this era of innovations where discoveries are made each day. As a researcher, one tries to do research work in their fields contributing to the existing knowledge vault in those subject areas. Every researcher built on the previous knowledge which is based on the thoughts of some great man or the other. Researchers are influenced by Sri Aurobindo’s philosophy and to achieve his goals, he gets influenced by his ideals and thoughts and helps in giving direction to his research, which is reflected somewhere in the researcher's research and his thoughts. Similarly, Sri Aurobindo’s Pondicherry Ashram is a laboratory of his educational ideas, he not only influenced the thoughts of the people but also influenced the personality of the researchers due to which he made his valuable contribution to society and the country by reflecting his thoughts in his research work. This research paper aims to investigate the integration of Sri Aurobindo's educational thought's thought experiments into the researcher's ongoing work. The researcher has based his research on an in-depth study of the educational thoughts of Sri Aurobindo. This research paper has discussed how the influence of the thoughts of current researchers plays a role in achieving the aims of their lives.